A Campus in Context: East Pakistan’s “Mass Upsurge” at Local, Regional, and International Scales - Samantha Christiansen (South Asia Multidisciplinary Academic Journal, 2019)
This article considers student activism at Dhaka University in the 1960s as a case study for considering student politics at multiple scales: local, regional, and international. In addition to providing a historical narrative of Dhaka’s engagement in the Mass upsurge campaign that led to the end of the Ayub Kahn regime, it also considers the ways this movement was informed by a sense of student power that extended beyond national borders.